Intercultural proposals for the university education of physics based on the awajún ancestral knowledge - Estela Urbina, Ronald Omar (2020)
At the National Intercultural University “Fabiola Salazar Leguía” in Bagua, the student population is made up of 50% of students from native Amazonian communities, mostly Awajún and to a lesser extent Wampis; and the other 50% are mestizos. The curricula of the professional careers of Civil Engineering and Biotechnology contemplate in their basic curricular structure the physics course, being this one of greater difficulty for the learning of the students, as evidenced in the academic records of the 2018-I cycles and 2019-I. The objective of the work was to formulate two intercultural didactic proposals for the learning of physics in university higher education, the first is the Awajún Ethnophysics, which consists of a look at common knowledge (ancestral knowledge) by the hand of Physics, through stories lived by the same students about their experiences, they constitute a workbook where ancestral knowledge is identified, as well as their systematized knowledge of the corresponding physics, in an intercultural environment of socialization between the Awajún and mestizo cultures that are evidenced in the university environment ; The second proposal is propedical, it is the Story-Based Learning, consisting of experiences and fictions of the student with the purpose of linking it to the disciplines of the physics of the aforementioned careers, in order to identify and characterize a physical phenomenon in an intercultural way. The two teaching proposals will improve the learning of physics in UNIFSL-B students from communities originating in the Amazon region. Peru.